Multicultural Values In Popular Indonesian Novels: Development Of Multicultural Values Through Indonesian Language Learning - Kusumawati, Yusmita; Rudy Rudy; Wahyu Ningsih (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study, which is library research, emphasizes identifying elements of cultural diversity in two popular novels, namely Laskar Pelangi (2005) by Andrea Hirata and Assalamualaikum Beijing by Asma Nadia (2013) to represent multicultural values ​​and suggest ways of developing These values ​​are through learning Indonesian for students. This research is seen as an important study to be developed in the world of education because the nation's next generation needs to be familiar with cultural diversity in order to foster multicultural values ​​such as tolerance, no prejudice, respect for differences and maintaining peace, especially in the diverse country of Indonesia. . Primary data for this qualitative research was collected from the two novels in the form of statements from the narrative in the novel. By utilizing Stuart Hall's theory of representation for data analysis and interpretation, the results of this study show that both authors show elements of diversity through the characters, language and cultural backgrounds in their novels. This study also suggests that the development of multicultural values ​​in education can be carried out through Indonesian language subjects by providing relevant reading and audio-visual materials and discussion activities in class. This study, which is library research, emphasizes identifying elements of diversity. culture in two popular novels, namely Laskar Pelangi (2005) by Andrea Hirata and Assalamualaikum Beijing by Asma Nadia (2013) to represent multicultural values ​​and explain how to develop these values ​​through learning Indonesian for students. This research is seen as an important study to be developed in the world of education because the nation's next generation needs to be familiar with cultural diversity in order to foster multicultural values ​​such as tolerance, no prejudice, respect for differences and maintaining peace, especially in the diverse country of Indonesia. . Primary data for this qualitative research was collected from the two novels in the form of statements from the narrative in the novel. By utilizing Stuart Hall's theory of representation for data analysis and interpretation, the results of this study show that both authors show elements of diversity through the characters, language and cultural backgrounds in their novels. This study also suggests that developing multicultural values ​​in education can be done through Indonesian language subjects by providing relevant reading and audio-visual materials and discussion activities in class.